Exploring nutrition capacity in Australia's charitable food sector. Issue 5 (23rd May 2016) - Wingrove, Kate; Barbour, Liza; Palermo, Claire
Abstract : Aim: The primary aim of this study was to explore the capacity of community organisations within Australia's charitable food sector to provide nutritious food to people experiencing food insecurity. A secondary aim was to explore their capacity to provide food in an environment that encourages social interaction. Methods: This qualitative research used an exploratory case study design and was informed by a nutrition capacity framework. Participants were recruited through SecondBite, a not‐for‐profit food rescue organisation in Australia. Convenience sampling methods were used. Semi‐structured interviews were conducted to explore the knowledge, attitudes and experiences of people actively involved in emergency food relief provision. Transcripts were thematically analysed using an open coding technique. Results: Nine interviews were conducted. The majority of participants were female (n = 7, 77.8%) and worked or volunteered at organisations within Victoria (n = 7, 77.8%). Results suggest that the capacity for community organisations to provide nutritious food to their clients may be limited by resource availability more so than the nutrition‐related knowledge and attitudes of staff members and volunteers. Conclusions: Australia's charitable food sector plays a vital role in addressing the short‐term needs of people experiencing food insecurity. To ensure the food provided to people experiencing food insecurity is nutritious and provided in an environment that encourages social interaction, it appears that the charitable food sector requires additional resources. In order to reduce demand for emergency food relief, an integrated policy approach targeting the underlying determinants of food insecurity may be needed.